Biology and conservation of wild felids - Macdonald, David W. (David Whyte); Loveridge, Andrew J. (Oxford biology., 2010)
This advanced textbook brings together a unique network of the world's most respected and knowledgeable experts to provide a review of the biology and conservation of wild felids, and detailed case-studies from species investigations worldwide.